Mechanical Properties of Endospermum diadenum sp. Grown in Sarawak - Nur Syahina, Yahya; Gaddafi, Ismaili (Teejas Publishers, 2015)
Timber is a renewable resource and preferred as building and construction material due to physical, mechanical, and has an aesthetically performance. However, timber varies due to its own property and proposes. The quality of the timber has a strong influence on the quality and value of timber products. Therefore, this study will be conducted to learn about mechanical strength properties of Terbulan (Endospermum diadenum sp.) fast-growing timber according to BS 373: 1957 Methods of Testing Small Clear Specimens of Timber. Instead of strength property, this study will be determined the suitable utilization of Terbulan timber for the construction industry. The test will be conducted on both conditions which are green and air-dry condition. Generally, Terbulan species is a fast-growing timber in Sarawak. From the point of view, the strength properties parameters such as basic density, modulus of rupture (MOR), modulus of elasticity (MOE) and compressive strength of Terbulan timber will be reviewed to determine the effectiveness of the species in the construction field. As a result of the analysis, it is found that Terbulan timber at the air-dry condition for MOR, MOE and compression parallel to grain reported with 84.17 N/mm², 10217.79 N/mm² and 28.94 N/mm² respectively. Terbulan is categorized in light hardwood timber and conclusion, related products are confined at the beginning it is a steel and concrete replacement that is mostly used in structure such as light construction, furniture and joinery.